TREATMENT OF INFANTS WITH REPEATED BACTERIAL INFECTIONS OF RESPIRATORY TRACT AND ENT-ORGANS WITH LYSATES MIXTURE - E.V. Vlasova; I.A. Tuzankina; V.N. Shershnev; M.A. Bolkov ("Paediatrician" Publishers LLC, 2009)
The article presents the results of a study, evaluating effectiveness of therapeutic use of bacterial lysates for the topical administration (IRS 19) in children under the age 3-9 months old. All children had repeated bacterial diseases of ENT-organs and respiratory tract; it is the clinical sign of immunological reactivity disorder in infants, which is estimated as so-called «syndrome of anti-infection defense disorder». Administration of drug resulted in decrease of rate and duration of infectious episodes in upper and lower airways, excluded the need of antibacterial treatment of these children. This effect is concerned with increase of resistance of children's organism and indirect correction of previously detected immune disorders. Key words: infants, infections of respiratory tract, disorders of anti-infection defense, bacterial lysates mixture. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(5):40-46)